2012
DOI: 10.1080/01639269.2012.713845
|View full text |Cite
|
Sign up to set email alerts
|

Whose Hands Ply the Strands? Survey of Eastern Michigan University Psychology Faculty Regarding Faculty and Librarian Roles in Nurturing Psychology Information Literacy

Abstract: The Association of College and Research Libraries developed information literacy standards and associated performance indicators for undergraduate psychology students. A survey of tenure-track faculty members and full-time lecturers in the PsychologyDepartment at Eastern Michigan University was conducted to discover how those professors viewed the importance of these indicators, and how those professors perceived their role, as well as the role of librarians, in supporting instruction that develops those skill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
4
1
Order By: Relevance
“…Information literacy no longer “belonged” to the library and librarians no longer led the charge to promote information literacy on campus. Instead, librarians transitioned their focus to supporting faculty as they incorporated information literacy skill development in their courses and assignments (Stanger, 2012).…”
Section: Framing Collaboration Through Conversationmentioning
confidence: 99%
“…Information literacy no longer “belonged” to the library and librarians no longer led the charge to promote information literacy on campus. Instead, librarians transitioned their focus to supporting faculty as they incorporated information literacy skill development in their courses and assignments (Stanger, 2012).…”
Section: Framing Collaboration Through Conversationmentioning
confidence: 99%
“…The only information literacy performance indicator the faculty believed the librarians were more responsible for teaching than they was "student constructs and implements effectively designed search strategies" (Stanger, 2012, p. 123). The conclusions of Housewright et al (2013) and Stanger's (2012) contradict the findings in this study. The participants in this study did not prioritize their instructional responsibilities of teaching information literacy competencies over librarians.…”
Section: Students Information Literacycontrasting
confidence: 67%
“…Some of the indicators included being able to access needed information, being able to evaluate information for uniqueness, and being able to utilize information to create a new idea. Stanger (2012) found that faculty believed they were more responsible than the librarians were for helping students meet 10 of the 11 information literacy performance indicators. The only information literacy performance indicator the faculty believed the librarians were more responsible for teaching than they was "student constructs and implements effectively designed search strategies" (Stanger, 2012, p. 123).…”
Section: Students Information Literacymentioning
confidence: 99%
“…10 Keith Stanger surveyed psychology faculty about the importance of ACRL's psychology IL performance indicators being part of the curriculum and found that ten out of the eleven indicators (ranging from need for information to communicating research effectively) were of great or very great importance. 11 Laura Saunders also concluded that "faculty members overwhelmingly believe that information literacy is important for their students." 12 Yevelson-Shorsher and Bronstein's interviews with faculty revealed that faculty members were aware of the obstacles students face when accessing and using information, and faculty understood the significance of developing IL skills.…”
Section: Faculty Views Of Information Literacymentioning
confidence: 99%